Impact of Enterprise Digital Transformation on the Efficiency of Total Factor Energy Utilization: -- From the Perspective of Differences in Enterprise Energy Efficiency - Zhang, Yaxuan; Zhang, Peiyao; Li , Zeyang; Sun, Danying (Transactions on Economics, Business and Management Research, 2024)
With the advent of the information age and the rapid progress of technology, it has become inevitable for enterprises to move towards digital transformation. Energy is one of the most vital material bases for national economic and social development, which plays a vital role in national economic growth. How to use energy efficiently has been the core factor to measure the sustainable development potential of an enterprise. Based on the data of listed companies in China, this paper empirically analyzes the impact of enterprise informatization on energy efficiency from different perspectives. Studies have shown that the degree of enterprise informatization has a direct relationship with its energy efficiency. At present, the overall informatization of enterprises in various regions of China is low. However, with the continuous popularization of digital technology and applications, it has a certain inhibitory effect on enterprise energy consumption, with the effect becoming more and more apparent. Especially during the digital transformation, the role of state-owned enterprises in promoting total factor energy consumption has been more significant. Therefore, from the perspective of digital transformation, it is of great significance to study the energy efficiency of state-owned enterprises. This research explores the significant differences in energy efficiency among various industries, and the adoption of digital transformation strategies will help narrow these differences and further promote energy efficiency improvement across the industry. In addition, through the analysis of typical cases, this topic reveals the main problems faced by enterprises in the process of digital transformation and their causes, which puts forward corresponding countermeasures and suggestions. This study can provide a solid theoretical basis for the positive role played by Chinese enterprises and related departments during the digital transformation.